USING INTERNET SITE AS TEACHING MODEL IN ENHANCING ENGLISH VOCABULARY FOR INDEPENDENT LEARNERS - Yeni Andikasari; Herri Setiawan (UNIVERSITAS INDO GLOBAL MANDIRI)
English language learners in high education institutions believe that vocabulary learning is difficult and complicated. At the university level, learners are forced to make conscious effort to learn vocabulary outside of the classroom because of the learning time in the classroom is limited. Consequently, the learners play an important role in developing and enhancing their vocabulary. now, surving on the Internet has been the most popular way to learn English because it is convenient as well as entertaining. It saves a lot of time. beside that Some websites provide beautiful illustrations to learn English so the learners learn by fun. A few websites supply amusing games and online language exercises to attract attention thereby helping them learn English effectively. Having been inspired from article by Dr.Vangeepuram Sreenathachary 2011, about using Internet in improving one’s english language skills and supported by some finding of Marc Rosenberg adapted Strategies for delivering knowledge in the digital Age by Rosenberg, M. J,2001, authors of This paper aims at using internet site as a teaching model to enhancing learners English vocabulary. The instructional plan covers the objectives, materials, activities and assessment. Instructional strategies to use quesioner sheet, guided and reflective discussion,web site link. Key words: Internet site, Independent Learners, Teaching model,Vocabulary